Appraisal of Thermomechanical Performance of Aluminum Metal Matrix Composites Using Stir Casting Technique. (8th October 2022) - Periasamy, K.; Ganesh, S.; Chandra Kumar, S.; Nandhakumar, S.; Thirugnanasambandham, T.; Gurmesa, Murtesa Dabesa
Abstract : The advance of aluminum alloy-based matrix composites is becoming indispensable in several applications like automobiles, aerospace, electronics, and structural industries due to the benefits over conventional materials such as lightweight, high strength, and high hardness value. The main aim of the work is to study the thermomechanical characteristics (heat transfer rate, convective heat transfer coefficient, and tensile strength) of an aluminum (AA7075) alloy nanocomposite containing 0 wt%, 3 wt%, 6 wt%, and 9 wt% of nano SiC particles (50 nm) by the stir casting technique. The thermomechanical performance of AA7075 alloy nanocomposite is obtained by pin fin apparatus and followed by ASTM test standards. The composite contained 9 wt% nano SiC and was found to have superior thermomechanical characteristics.